USAGE OF ATHLETES AS ENDORSERS - Stevo Popović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The objective of this study represent the usage of athletes as endorsers, while the main goal refers the requirement that endorsement should be presented to potential users as less simpler and on more attractive way. The main tasks of this study are, the first explaining what endorsement means, then presenting the examples of good practice as well as drawing attention to the need for usage of athletes as endorsers. During the making of this study, the author used descriptive method with consulting of competent literature. The previous author' experience in this field was also so useful. Moreover, the author used the analytic method and parallel method that is the most productive if you make some inferences about some appearance.